PERLINDUNGAN HUKUM TERHADAP PENYELENGGARA PELAYANAN KESEHATAN HEMODIALISA DI RUMAH SAKIT - Lilik Fitriana; Dr. Eddy Asnawi; Dr. Yeni Triana (Jurnal Ilmiah Advokasi, 2022)
To ensure legal protection for hemodialysis service providers, both for hospitals as service providers, medical personnel and health workers as service providers, the Government has stipulated Minister of Health Regulation Number 812/Menkes/PER/VII/2010 concerning the Implementation of Dialysis Services in Service Facilities. Health. As long as doctors or health workers in carrying out their duties in providing hemodialysis health services to patients are still guided by professional standards, medical service standards and standard operating procedures, legal protection for the practice of these services is a right guaranteed by law. Furthermore, there are 3 (three) pillars so that doctors and health workers become professionals, namely obeying the law, discipline, and ethics. To ensure the implementation of quality hemodialysis services and provide legal protection for each hemodialysis service provider.Keywords:Â Hemodialysis;Â Legal Protection; Service Provider.Â